2015
DOI: 10.1111/bjso.12105
|View full text |Cite
|
Sign up to set email alerts
|

One of few or one of many: Social identification and psychological well‐being among minority youth

Abstract: Feeling belongingness with small social groups such as the family or a group of friends predicts psychological well-being. Acculturation research has argued for similar effects of belongingness with large social groups. In particular, a strong ethnic identity is assumed to improve psychological well-being among members of minority groups, but this conclusion has been drawn based on cross-sectional data. This study uses three-wave longitudinal data collected among adolescents from ethnic minority groups (N = 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 116 publications
1
17
1
Order By: Relevance
“…Among two groups of voluntary migrants in Spain, namely, Colombians and Romanians, we did not find a significant relationship between host national identification and well-being, thereby failing to find support for the RDIM for these groups. These results are in line with some other studies that did not find a relationship between national identity and well-being among minorities (Bratt, 2015;Jasinskaja-Lahti et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Among two groups of voluntary migrants in Spain, namely, Colombians and Romanians, we did not find a significant relationship between host national identification and well-being, thereby failing to find support for the RDIM for these groups. These results are in line with some other studies that did not find a relationship between national identity and well-being among minorities (Bratt, 2015;Jasinskaja-Lahti et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…For instance, in the case of immigrants, Jasinskaja‐Lahti et al () found that ethnic identification was unrelated to both perceived discrimination and stress symptoms. In the same vein, in Bratt's study () with minority youth, there was no link between ethnic identity and well‐being. Cronin et al () did not find a direct effect of perceived discrimination on higher ethnic identification over time among Latino students either.…”
Section: Ethnic Identification As Social Cure?mentioning
confidence: 87%
See 3 more Smart Citations